PENGARUH KOMUNIKASI YANG EFEKTIF TERHADAP KINERJA KARYAWAN PADA PT. FEDERAL INTERNATIONAL FINANCE (FIF) DI PAMULANG - Achmad Rozi (Faculty of Economics and Business, Universitas Malikussaleh, 2020)
This study aims to determine the effect of effective communication on employee performance at PT. Federal International Finance (FIF) in Pamulang. The method used was explanatory research with a sample of 88 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study communication variables obtained an average score of 3.42 with good criteria. Employee performance variables obtained an average score of 3.79 with good criteria. Communication has a positive and significant effect on employee performance with a regression equation value of Y = 8.691 + 0.854X, and the correlation coefficient value is 0.777 or has a strong relationship with the determination value of 60.4%. Hypothesis testing obtained significance of 0,000 0.05.